Shifts in the beveridge curve - Peter A. Diamond; Ayşegül Şahin (Federal Reserve Bank of New York, 2014)
This note puts the current shift in the Beveridge curve into context by examining the behavior of the curve since 1950. Outward shifts in the Beveridge curve have been common occurrences during U.S. recoveries. By itself, the presence of a shift has not been a good predictor of whether the unemployment rate at the end of the expansion following a shift was higher or lower than that in the preceding expansion.
Keywords: E24; J60; 330; Beveridge curve; unemployment; vacancies